New Sulfur-Containing Polyarsenicals from the New Caledonian Sponge Echinochalina bargibanti - Tähtinen P; Guella G; Saielli G; Debitus C; Hnawia E; Mancini I (MDPI, 2022)
Arsenicin A (C3H6As4O3) was isolated from the New Caledonian poecilosclerid sponge Echinochalina bargibanti, and described as the first natural organic polyarsenic compound. Further bioguided fractionation of the extracts of this sponge led us to isolate the first sulfur-containing organic polyarsenicals ever found in Nature. These metabolites, called arsenicin B and arsenicin C, are built on a noradamantane-type framework that is characterized by an unusual As-As bonding. Extensive NMR measurements, in combination with mass spectra, enabled the assignment of the structure for arsenicin B (C3H6As4S2) as 2. The scarcity of arsenicin C and its intrinsic chemical instability only allowed the collection of partial spectral data, which prevented the full structural definition. After the extensive computational testing of several putative structures, structure 3 was inferred for arsenicin C (C3H6As4OS) by comparing the experimental and density functional theory (DFT)-calculated H-1 and C-13 NMR spectra. Finally, the absolute configurations of 2 and 3 were determined with a combined use of experimental and time-dependent (TD)-DFT calculated electronic circular dichroism (ECD) spectra and observed specific rotations. These findings pose great challenges for the investigation of the biosynthesis of these metabolites and the cycle of arsenic in Nature. Arsenicins B and C showed strong antimicrobial activities, especially against S. aureus, which is comparable to the reference compound gentamycin.